ESG Disclosure Research: A Bibliometric Analysis of Sustainability Reporting Trends - Loso Judijanto (West Science Social and Humanities Studies, 2026)
The importance of Environmental, Social, and Governance (ESG) disclosure has been gaining prominence owing to the growing sustainability concerns across the globe. The objective of this study is to analyze the intellectual structure, evolution of research, and trends emerging in ESG disclosure literature. Data have been gathered from the Scopus database on the basis of the use of suitable keywords for ESG disclosure, sustainability reporting, and corporate sustainability. Bibliometric analysis techniques such as publication trend analysis, citation analysis, keyword co-occurrence analysis, thematic evolution analysis, density visualization, and collaboration network analysis have been performed using VOSviewer. Results show that there is a notable trend in the area of ESG disclosure literature owing to increased adoption of sustainability standards and regulations as well as sustainable investments. It has been found that the major themes in the area of ESG disclosure include sustainability reporting, ESG, sustainable development, corporate governance, and ESG performance. Furthermore, recent research trends have shifted toward emerging issues such as ESG regulation, greenwashing, sustainable finance, firm value, and investor responses. Citation analysis identifies mandatory sustainability reporting, ESG performance, governance mechanisms, and the financial implications of ESG disclosure as the primary intellectual foundations of the field. Collaboration analysis demonstrates that ESG disclosure research has expanded globally, with significant contributions from countries such as the United States, India, Italy, Indonesia, and European nations. This study contributes to the ESG literature by mapping the current research landscape, identifying influential contributions, and highlighting future research opportunities related to ESG standardization, reporting credibility, digital sustainability reporting, and sustainable corporate strategies.